TEARA: Educational Treatment of Children with ASD, mediated through augmented reality - Romero, Mónica R. (2022)
The treatments that used since the 1960 as educational proposals for children with autism spectrum disorder (ASD) are becoming obsolete over time. This research proposes an educational treatment for children with autism mediated through augmented reality called (TEARA), as a response to the challenges and constant change of a globalized world, which requires the establishment of new methods, strategies and treatments that allow improve the quality of life of these children with autism. The methodology was approached through a mixed, exploratory, descriptive, and purposeful study where a multidisciplinary team participated, we developed a training system called Hope, which reinforces and promotes teaching-learning processes, finally after several cycles of intervention, deep observation and the compilation of results, it was established that TEARA can be used by professionals, parents and people who accompany children with ASD.